Quantitative Momentum : A Practitioner's Guide to Building a Momentum-Based Stock Selection System /: A Practitioner's Guide to Building a Momentum-Based Stock Selection System. (2016) - Gray, Wesley R; Vogel, Jack R
No abstract available